2016
DOI: 10.1021/acs.analchem.5b04716
|View full text |Cite
|
Sign up to set email alerts
|

Visual Color-Switch Electrochemiluminescence Biosensing of Cancer Cell Based on Multichannel Bipolar Electrode Chip

Abstract: In this work, we developed a visual electrochemiluminescence (ECL) sensing platform based on a dual-bipolar electrode (D-BPE) array chip. The chip was composed of two arrays of BPEs and three separated arrays of reservoirs filled with buffer, Ru(bpy)3(2+)-TPrA and luminol solutions, respectively. Both BPEs served as ECL reporting platforms. By applying 6.0 V voltage, an array of orange electrochemiluminescence (ECL) signals belonging to Ru(bpy)3(2+) turned on. After adding DNAzyme and H2O2 in Ru(bpy)3(2+) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 22 publications
0
70
0
Order By: Relevance
“…ABTS can be effectively oxidized by H 2 O 2 and turns green in the typical colorimetric reaction. 39 In addition, as H 2 O 2 has a low redox potential, 40 the supplied driving voltage can also effectively promote the oxidation of ABTS in Rb and the deposition of PB at the Figure S4.…”
Section: Resultsmentioning
confidence: 99%
“…ABTS can be effectively oxidized by H 2 O 2 and turns green in the typical colorimetric reaction. 39 In addition, as H 2 O 2 has a low redox potential, 40 the supplied driving voltage can also effectively promote the oxidation of ABTS in Rb and the deposition of PB at the Figure S4.…”
Section: Resultsmentioning
confidence: 99%
“…Such a platform coupled to an amplification strategy allows to detect very small amounts of specific cell surface proteins . The detection of cancer biomarkers thanks to a BPE array chip was also demonstrated, thus opening the door to sensitive and reasonably cheap high‐throughput analytical detection on biochips .…”
Section: Bipolar Electrodes Operating In a Microchannelmentioning
confidence: 99%
“…An electrochemical cell (ECL cell, 20 × 12 mm, 2 mm thick, 600 μL) was designed by using ethylene-vinyl acetate copolymer as the insulating dielectric material. A 2 × 3 bipolar gold electrode was fabricated according to the reference 25 and the preparation process of the bipolar electrode system in this study is shown in Fig. S2 (Supporting Information).…”
Section: Fabrication Of Electrode Arraymentioning
confidence: 99%